Solution-processed carrier selective layers for high efficiency organic/nanostructured-silicon hybrid solar cells. Issue 9 (17th February 2016) - Kou, Ying-Shu; Yang, Song-Ting; Thiyagu, Subramani; Liu, Chien-Ting; Wu, Jia-Wei; Lin, Ching-Fuh
Abstract : We chose two kinds of carrier-selective layers to be applied in a hybrid solar cell device, and demonstrated that the PCE of Si/organic heterojunction solar cells can be improved to 13.23%. Abstract : The reduction of interface minority carrier recombination is regarded as a key performance indicator in improving the power conversion efficiency (PCE) of organic–inorganic hybrid solar cells. In this study, we chose two kinds of carrier-selective layers to be applied in a hybrid solar cell device. A hole selective transporting layer of N, N ′-bis(3-methylphenyl)- N, N ′-diphenylbenzidine (TPD) was added to the interface between Si nanohole structures and PEDOT:PSS, and the electron selective layer cesium carbonate (Cs2 CO3 ) was added to the interface between the backside Si wafer and the rear Ti/Ag electrode. The main process used a clean and low-cost solution process, and the annealed temperature was under 140 °C. In addition, after we inserted these two carrier selective layers, the minority carrier lifetime was prolonged from 29.98 μs to 140.81 μs, indicating its significance in reducing the recombination rate. Eventually, we demonstrated that the PCE of Si/organic heterojunction solar cells can be improved to 13.23%.